Adapting the load-bearing structure of a gondola car for transporting high-temperature cargoes - Fomin, Oleksij; Lovska, Alyona; Khara, Maryna; Nikolaienko, Iryna; Lytvynenko, Andrii; Sova, Sergiy (Eastern-European Journal of Enterprise Technologies, 2022)
This paper determines the load on the load-bearing structure of a universal gondola car during the transportation of cargo with a temperature of 700 °C in it. It has been established that the maximum equivalent stresses, in this case, significantly exceed permissible ones. The maximum temperature of the cargo, at which the strength indicators of the carrying structure of the gondola do not exceed the permissible values, is 94 °C. At the same time, the temperature of the cargo transported in the cars by rail can be much higher. In this regard, in order to use gondola cars for the transportation of cargoes with high temperatures, it is possible to arrange them in heat-resistant containers of open type – flatcars. Therefore, in this study, a structure of the flatcar with convex walls has been proposed. Such configuration of the sidewalls makes it possible to increase the usable volume of the container by 8 % compared to the prototype. As a flatcar material, a composite with heat-resistant properties is used. To justify the proposed solution, the strength of a flatcar was calculated. It has been established that the maximum equivalent stresses in the carrying structure of the flatcar are about 300 MPa and do not exceed permissible ones. To determine the main indicators of the dynamics of the gondola car loaded with flats, its dynamic load was mathematically modeled. The calculation results showed that the accelerations that operate in the center of the mass of the load-bearing structure of a gondola car are about 1.5 m/s2. The vertical dynamics coefficient is 0.22. The estimated dynamics indicators are within the permissible values. The study reported here could contribute to improving the efficiency of the use of gondola cars and to further advancements in the design of innovative vehicles